Case Report: The First Reported Case of Bullous Lichen Planus-Systemic Lupus Erythematosus Overlap Syndrome - Liu, Yi; Liang, Xuelei; Wu, Haixuan; Zhuo, Fenglin (Frontiers in Medicine, 2021)
Introduction: Lichen planus (LP)/lupus erythematosus (LE) overlap syndrome is rarely seen in the clinic and has the characteristic clinical manifestations, histopathology, and immunopathology of LP and LE. This is the first reported case of bullous lichen planus (BLP)/systemic lupus erythematosus (SLE) overlap syndrome with hair loss as the first symptom. Case Presentation: A 48-year-old female presented with alopecia for half a year, and skin lesions accompanied by itching on her face, trunk, and limbs for 3 months. She had a history suggestive of photosensitivity. Laboratory tests and histopathology were performed for diagnosis. Histopathologic features of the upper arm and back of the hand were consistent with BLP, whereas the scalp lesion indicated LE. Laboratory examination indicated positive for ANA (1:160), leukopenia, increased urinary protein, decreased C3/C4, and normal BP180. The patient was given glucocorticoid combined with acitretin and immunosuppressive therapy after a definite diagnosis of BLP/SLE overlap syndrome. The patient’s lesions disappeared and a little new hair had regrown at the 2-year follow-up. Conclusion: This is the first reported case of BLP/SLE overlap syndrome which responded well to glucocorticoids, retinoids, and immunosuppressive drugs. Multiple biopsies from characteristic lesions will guide doctors to avoid misdiagnoses and delayed treatment.